Analysis of in-hospital mortality among ischemic stroke patients in Veresaev City Clinical Hospital - Dzhavgarat M. Murtazalieva; Aminat R. Zakariaeva; Tamara D. Soshina; Roman V. Shyrokii; Zaur S. Shogenov (ZAO "Consilium Medicum", 2023)
Background. Ischemic stroke (IS) is one of the most common cause of death in the world. The decline in stroke mortality is an important aim of medicine. The introduction of clinical guidelines for the management of patient with IS and transient ischemic attacks in adults in 2020 has made it possible to improve treatment for stroke patients in the Russian Federation. However, it is not completely understood whether the impact of introduction of clinical guidelines for decrease of stroke mortality. Aim. To compare and discuss causes of differences between stroke mortality rates in 2019 and 2022 in Veresaev City Clinical Hospital. Materials аnd methods. We compare the rates of in-hospital mortality among IS, frequency of thrombolytic therapy, mechanical thrombectomy, intermitted pneumatic compression, the incidence of pneumonia, hemorrhagic transformation, pulmonary thromboembolism and early activation in stroke between patients in 2019 and 2022 in Veresaev City Clinical Hospital. The study involved 1609 patients with IS in 2019, and 1429 patients with IS in 2022 in Veresaev City Clinical Hospital. We assessesed NIHSS to objectively rate severity of stroke and the modified Rankin Scale for measuring the degree of disability. Results. Initial stroke severity on NIHS scale was 9.6 in 2019 and 8.0 in 2022 (p0.05), stroke severity on NIHS scale at discharge was 7.8 in 2019 and 5.3 in 2022. Modified Rankin Scale at discharge was 1.95 in 2019 and 2.2 in 2022 (p0.05). Frequency of thrombolytic therapy was 8.6% in 2019 and 14.1% in 2022 (p0.05); 3.7% of patients undergone of mechanical thrombectomy in 2019 and 6.7% patients in 2022 (p0.05). In 2019 patients werent undergone of mechanical thrombectomy from 6 to 24 hours after stroke; 14 patients in 24-hour therapeutic window undergone of mechanical thrombectomy in 2022 (15.5%). There are no intermitted pneumatic compression in 2019; 18% of patients undergone intermitted pneumatic compression in 2022 (p0.05). Early activation used in 30% of patients in 2019 and 96% of patients in 2022 (p0.05). Pulmonary thromboembolism frequency was 26% in 2019 and 1% (p0.05). In-hospital mortality from IS was 19.9% in 2019 and 5.7% in 2022 (p0.001). Conclusion. Accurate adherence to clinical guidelines demonstrated decline of in-hospital mortality rate from IS.